Efficient Removal of Heavy Metal Ions in Wastewater by Using a Novel Alginate-EDTA Hybrid Aerogel - Min Wang; Zhuqing Wang; Xiaohong Zhou; Shikun Li (Applied Sciences, 2019)
In this study, we prepared a novel calcium alginate-disodium ethylenediaminetetraacetate dihydrate hybrid aerogel (Alg-EDTA) by chemical grafting and vacuum-freeze-drying to remove heavy metal ions from wastewater. Experimental results show that the as-prepared Alg-EDTA adsorbent has a high affinity for heavy metal ions, such as Cd2+, Pb2+, Cu2+, Cr3+, and Co2+, and can adsorb >85% of metal ions from the corresponding solution. Alg-EDTA also exhibits high selectivity toward Cd2+, and the maximum adsorption capacity for Cd2+ reached 177.3 mg/g, which exceeds the adsorption capacity of most reported Cd2+-adsorbents. Adsorbent regeneration can be achieved by a simple acid-washing process, and adsorption performance of Alg-EDTA remains stable after repeated use. All these findings indicate that Alg-EDTA has a promising prospect in the treatment of heavy metal ions wastewater.